ASERTIVITAS DAN SUBJECTIVE WELL-BEING PADA MAHASISWA DI MASA PANDEMI COVID-19 - Ika Apriati Widya Puteri (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ABSTRACT: ASSERTIVENESS AND SUBJECTIVE WELL-BEING ON UNIVERSITY STUDENT IN THE COVID-19 PANDEMIC TIME This year, the global Covid-19 pandemic hit the world and affected various aspects of life, as well as in the world of education. The pandemic that is there is causing some psychological symptoms in the majority of people. The adaptation to this new situation affects students' subjective well-being. One of the factors related to subjective well being is assertiveness. The purpose of this study was to determine the relationship between assertiveness and subjective well-being among college students, especially in the global Covid-19 pandemic situation. This research was conducted on 49 students of The Teacher Training and Education Faculty, Widya Gama Mahakam University Samarinda. This study uses an instrument of assertiveness scale, the scale of Satisfaction with Life Scale, and the Scale of Positive and Negative Experience. The analysis was performed using Pearson's product moment correlation technique. The results showed that there was no relationship between assertiveness and subjective well-being in the students of the Teaching and Education Faculty, Widya Gama Mahakam University Samarinda. Keywords: Assertiveness, Subjective Well-Being, University Student Tahun ini, pandemi global Covid-19 melanda dunia dan mempengaruhi berbagai aspek kehidupan, begitu pula dalam dunia pendidikan. Pandemi yang ada menimbulkan beberapa gejala psikologis pada sebagian besar orang. Adaptasi terhadap situasi yang baru ini mempengaruhi kesejahteraan subjektif (subjective well-being) mahasiswa. Salah satu faktor yang berhubungan dengan subjective well-being  adalah asertivitas. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara asertivitas dan subjective well-being pada mahasiswa, khususnya pada situasi pandemi global Covid-19. Penelitian ini dilakukan terhadap 49 mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda. Penelitian ini menggunakan instrumen skala asertivitas, skala Satisfaction with Life Scale, dan Scale of Positive and Negative Experience. Analisis dilakukan dengan teknik korelasi product moment dari Pearson. Hasil penelitian menujukkan bahwa tidak ada hubungan antara Asertivitas dan Subjective Well-Being pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda. Kata Kunci: Asertivitas, Subjective Well-Being, Mahasiswa